2018
DOI: 10.1088/1674-1056/27/12/127503
|View full text |Cite
|
Sign up to set email alerts
|

Realization of artificial skyrmion in CoCrPt/NiFe bilayers

Abstract: Skyrmion, as a quasi-particle structure, has attracted much attention due to its potential applications in future spintronic devices. Artificial skyrmion structure has aroused great interest as it can be stabilized at room temperature, without needing to incorporate materials with Dzyaloshinskii-Moriya interaction (DMI) into it. In this paper, it is found that the artificial skyrmion structure can be realized in CoCrPt/NiFe bilayers by micromagnetic simulations. The critical magnetic field of the core decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Considering the FM IEC, an skyrmion-like spin texture can be formed across both the top dot and bottom film as reported previously. [28,[34][35][36] Our SAF multilayer is non-compensated and the IEC is antiferromagnetic type.…”
Section: Resultsmentioning
confidence: 97%
“…Considering the FM IEC, an skyrmion-like spin texture can be formed across both the top dot and bottom film as reported previously. [28,[34][35][36] Our SAF multilayer is non-compensated and the IEC is antiferromagnetic type.…”
Section: Resultsmentioning
confidence: 97%
“…It can be seen that the infrared transmittance of the crystal decreases obviously with the increase of Al doping content. The infrared transmittance of crystals can be calculated by the following formula [41]:…”
Section: Effect Of Al On the Dislocation Of Ga 086 In 014 Sb Crystalmentioning
confidence: 99%
“…Similar simulation results in Co/CoPt bilayers were reported by Si et al [ 28 ] Three different spin textures, the I‐type vortex, the Bloch‐type skyrmion, and the II‐type vortex, were found to depend on three different PMA constants of the CoPt layer. The material parameters chosen for this study are those of the CoCrPt/NiFe bilayers, [ 27 ] which are different from those of the Co/CoPt bilayer reported by Si et al [ 28 ]…”
Section: Stability Of the Artificial Skyrmionmentioning
confidence: 99%
“…In our previous work, it was found that the Bloch‐type skyrmion was stable in the CoCrPt/NiFe bilayer. [ 27 ] As shown in Figure 2 a–d, at the beginning, set the magnetic moments to a random distribution. Applying a 400 mT magnetic field, all the magnetic moments were reversed.…”
Section: Simulation Modelmentioning
confidence: 99%